2022
DOI: 10.1111/prd.12436
|View full text |Cite
|
Sign up to set email alerts
|

Oral bacteria, oral health, and adverse pregnancy outcomes

Abstract: Periodontal disease is one of the most common chronic inflammatory disorders that affect tissues surrounding the tooth. 1 Generally, periodontal disease can be classified into two stages based on the severity: gingivitis and periodontitis. Gingivitis is a mild form characterized by inflammation of the soft tissues surrounding a tooth or the gingiva, while periodontitis is a more severe form characterized by destruction of supporting structures of the teeth including periodontal ligament, bone, cementum, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 81 publications
(149 reference statements)
0
20
0
Order By: Relevance
“…Multiple epidemiological studies indicate an association between periodontitis and adverse pregnancy outcomes, such as preterm birth, low birthweight, miscarriage, preeclampsia, intra‐uterine growth retardation, neonatal sepsis, and stillbirth. Xu and Han 52 review and discuss the epidemiological evidence as well as mechanistic and interventional/therapeutic studies that could suggest a causal relationship between periodontitis and pregnancy complications. The authors cite a recent case‐control study that showed that the prevalence of preterm delivery increased with increasing severity of gingivitis or periodontitis, thus enhancing the plausibility of causality.…”
Section: Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Multiple epidemiological studies indicate an association between periodontitis and adverse pregnancy outcomes, such as preterm birth, low birthweight, miscarriage, preeclampsia, intra‐uterine growth retardation, neonatal sepsis, and stillbirth. Xu and Han 52 review and discuss the epidemiological evidence as well as mechanistic and interventional/therapeutic studies that could suggest a causal relationship between periodontitis and pregnancy complications. The authors cite a recent case‐control study that showed that the prevalence of preterm delivery increased with increasing severity of gingivitis or periodontitis, thus enhancing the plausibility of causality.…”
Section: Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…Accordingly, changes in metabolism and hormone system, alongside with changed lifestyle and nutritional behaviors often lead to gingival and mucosal changes [ 3 ]. This might also include a potential risk for the unborn child; although discussed controversially, microorganisms and pro-inflammatory cytokines can pass the placental barrier, potentially leading to complications and adverse pregnancy events [ 4 ]. Moreover, there is a relationship between oral health of mother and child, especially with regard to dental caries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that a single intervention type may be insufficient to address periodontal inflammation or control oral bacterial load, and performing a combination of multiple 10.3389/fmed.2022.963956 approaches is more effective. At the same time, maintenance of health oral status throughout the gestation is recommended, rather than the "one-time deal" (98,99).…”
Section: Macronutrientsmentioning
confidence: 99%